Kepemimpinan Kepala Sekolah yang Efektif Berlandaskan Prinsip Kepemimpinan Nabi Muhammad SAW - Deswita, Elvi; Asmendri, Asmendri (Lembaga Yasin AlSys, 2022)
The success of a school principal is greatly influenced by his effectiveness in leading a school. An effective leader is a leader who is able to mobilize and motivate others to do what they want in order to achieve common goals. The school principal in leading an educational institution must be based on the principles of education management and the principles exemplified by the prophet Muhammad SAW. The purpose of this research is to see the implementation of effective leadership principles in schools. The research method used is library research. The results of this study indicate that to produce a superior school management requires an effective leader who applies the principles of leadership of the prophet Muhammad SAW